Intestinal immune responses to commensal and pathogenic protozoa - Sardinha-Silva, Aline; Alves-Ferreira, Eliza V. C.; Grigg, Michael E. (Frontiers in Immunology, 2022)
The physical barrier of the intestine and associated mucosal immunity maintain a delicate homeostatic balance between the host and the external environment by regulating immune responses to commensals, as well as functioning as the first line of defense against pathogenic microorganisms. Understanding the orchestration and characteristics of the intestinal mucosal immune response during commensal or pathological conditions may provide novel insights into the mechanisms underlying microbe-induced immunological tolerance, protection and/or pathogenesis. Over the last decades, our knowledge about the interface between the host intestinal mucosa and the gut microbiome has been dominated by studies focused on bacterial communities, helminth parasites and intestinal viruses. In contrast, specifically how commensal and pathogenic protozoa regulate intestinal immunity is less well studied. In this review, we provide a comprehensive overview of mucosal immune responses induced by intestinal protozoa, with a major focus on the role of different cell types and immune-mediators triggered by commensal (Blastocystis spp. and Tritrichomonas spp) and pathogenic (Toxoplasma gondii, Giardia duodenalis, Cryptosporidium parvum) protozoa. We discuss some of their peculiarities and similarities, and specifically how they modulate innate and adaptive immune responses induced in experimental models of infection.